Risk assessment of Occupational Safety & Heath (OSH) hazards at small and medium enterprise (SME) - Abdol Rahman, Mohd Nasrull; Samin, Nor Laila Hanum (2022)
Most of SMEs industries refuse to provide and conduct safety program for the employees in order to cut the budget. Thus, this industries are exposed to the occupational safety and health (OSH) hazards. Therefore performing the Hazard Identification, Risk Assessment and Risk Control (HIRARC) method are important to control the hazards. The objective of this research was to review occupational safety and health hazards related to small to medium enterprises (SMEs) industry. Besides that, this research conducted to identify the OSH hazards related to the selected SMEs industry using HIRARC method and to propose a suitable risk control to prevent the hazards. The selected SME industries are located in Rompin, Negeri Sembilan in production of cendol. For this research, two method of hazard identification were selected that are workplace inspection and hazard identification checklist. A total of 8 hazards were identified from the production process. 50% of the risk level were classified as low and 50% classified as medium risk level. The most hazardous work activity is related to ergonomic problem that is back pain as most of the activities were repetitive for a long time. As a conclusion, recommendation has been proposed to eliminate the identified hazards such as elimination, engineering control and personal protective equipment based on the hierarchy of risk control.